Role of Hypothyroidism on Ovarian and Uterine Morphology in Sonography of Women at Reproductive Age - Nazanin Farshchian; Rozita Naseri; Nikzad Farshchian; Parisa Bahrami Kamangar; Mansour Rezaei (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2021)
Introduction: Hypothyroidism is a clinical syndrome due to thyroid hormones deficiency that can affect reproductive function. Regarding to the prevalence of hypothyroidism and infertility, this study was performed with aim to evaluate the role of hypothyroidism on uterine and ovarian morphology. Methods: In this cohort study which was performed in the clinic of Kermanshah Imam Reza Hospital in 2017, 161 women with subclinical hypothyroidism were selected as exposed group based on TSH level and 161 healthy women were randomly selected as the control group. On the 14th day of the menstrual cycle, ultrasounds were taken from uterus and ovary in two groups and the data were recorded in special data collection form. Data were analyzed by SPSS software (version 16) and Fisher, Kolmogrov Smironov, and independent-t test. p < 0.05 was considered statistically significant. Results: There were menstrual irregularities (P=0.01), reduced number of pregnancies or lack of pregnancy (P=0.017), increased endometrial thickness (P=0.01), increased volume and number of follicles in the ovaries and reduced size of ovarian follicles (P=0.01) in the exposed group compared to the control group, however, hypothyroidism had no effect on the size of the uterus (P=0.406).  Conclusion: Hypothyroidism, by increasing the size of the ovaries and the number of the follicles and reducing follicular size causes change in the morphology of the ovaries similar to PCOD, and can be a cause of menstruation irregularity in women of reproductive age.